Squids Fishing (Stenoteuthis oualaniensis) as the Main Livelihood of Motto Village Citizens, North Lembeh, Bitung City - Muhammad Zainul Arifin; Rudi Saranga; Samuel Hamel; Jul Manohas; Elsari T Putri; Lusje Antou (Departemen Teknik Kelautan Universitas Hasanuddin, 2026)
Squid fishing by Motto Village fishermen is a hereditary cultural fishing and has been going on for a long time. The research on squid fishing of Motto village is essential to know how squid harvested and captured. The purpose of this study was to identify squid fishing in the waters of the Motto Village. The method used in this research is a descriptive research method. The research was conducted during September - November 2021. Data was collected through observation and interviews. The results obtained that squid fishing is one day fishing in their traditional fishing ground. Fishermen in good weather do fishing operation 20-25 times of fishing trip monthly. This squid fishing activity in Motto waters is still profitable. There are two marketing flow of squid in the Motto waters. The squid is sold to market trader/factory or to traditional market. The added value product of squid of Motto needs to be suggested and implemented for their new income, this has not been done by community.